PEREMPUAN DALAM KUNGKUNGAN FUNDAMENTALISME - Sovia, Sheyla Nichlatus (Dialogia: Jurnal Studi Islam dan Sosial, 2015)
Absract: Islam is honored women. However, in reality the women role are often marginalized in the areas of political, economic, social, cultural, and education, in public and domestic. According to the writer, women become paralyzed by the religious authorities and the social structures that despise against women and consider women did not have any role in social life. Generally, religious authorities and social structures live fundamentalism. Women and regain control authority patriarchal family is the ultimate goal in a fundamentalist utopia. For them, women are a symbol of the purity of religion, so that women are the first group to experience the 'purification' or 'cleaning'. Fundamentalists feel that because of differences in natural and biological, women should have different roles in the family and society. Even so, there are some women who support fundamentalist movements with practices such as polygamy willingly and others. The women who participated in a range of fundamentalism is usually caused by several things, such, firstly, because of ideology through religious doctrines; secondly, because of social factors and the thirdly due to economic factors. Keywords: Marginalisasi, Us}u>liyah, Dakwah dan Domesti